Impact of Ownership Structure and Board Structure on the Performance of Non-Financial Institutions of Nepal - DC, Samir; Basnet, Sanila (Nepalese Journal of Finance, 2024)
This study examines the impact of ownership structure and board structure on the performance of non-financial institutions of Nepal. Return on assets and return on equity are selected as the dependent variables. The selected independent variables are concentrated ownership, institutional ownership, managerial ownership, board size, CEO duality, board independence, gender inclusive on board, and existence of audit committee on board. The study is based on secondary data with 105 observations from 16 listed non-financial institutions. The data were collected from annual reports of selected non-financial institutions. The correlation coefficients and regression models are estimated to test the significance and importance of ownership structure and board structure on the performance of non-financial institutions of Nepal. The study showed that board size has a positive impact on return on equity and return on assets. It indicates that larger the board size, higher would be the return on equity and return on assets. Similarly, board independence has a positive impact on return on equity and return on assets. It indicates that increase in number of independent directors on the board leads to increase in return on equity and return on assets. Likewise, gender inclusive on board has a positive impact on return on equity and return on assets. It indicates that presence of female director in the board leads to increase in return on equity and return on assets. Further, existence of audit committee on board has a positive impact on return on equity and return on assets. It indicates that increase in audit committee members leads to increase in return on equity and return on assets. In addition, CEO duality has a negative impact on return on equity and return on assets. It indicates that if one person serves as the chairman of the board of directors’ leads to decrease in return on equity and return on assets. Likewise, concentrated ownership has a positive impact on return on equity and return on assets. It indicates that higher the concentrated ownership, higher would be the return on equity and return on assets. Moreover, institutional ownership has a positive impact on return on equity and return on assets. It indicates that higher shares held by entities, higher would be the return on equity and return on assets. Further, managerial ownership has a positive impact on return on equity and return on assets. It indicates that higher the shares held by directors of board and management, higher would be the return on equity and return on assets.